Factors associated with metabolic syndrome in severe mental illness patients at selected government hospitals in the Klang Valley, Malaysia - Zulkefli, Nur Sabrina (2016)
Mental illness is a huge public health burden in the modern world. It has a broad range of illness with different symptoms, in which it is generally characterized by a combination of abnormal thoughts, emotions, behaviors and relationships with others. Mental illness exists on a continuum of severity ranging from mild, moderate to severe. Severe mental illness includes schizophrenia, bipolar disorder, and major depressive disorder (MDD). Patients with severe mental illness are at risk of developing metabolic syndrome (MetS). Metabolic syndrome is a cluster of cardiovascular risk factors, including insulin resistance, abdominal obesity, dyslipidemia, and hypertension. Few research have examined MetS and the contributing factors to its development among severe mental illness patients in Malaysia. This cross-sectional study aimed to determine factors associated with MetS in severe mental illness patients attending psychiatric outpatient clinics in Hospital Kuala Lumpur and Hospital Kajang. A total of 151 outpatients (45.0% males and 55.0% females) with a mean age of 41.84±12.19 years fulfilled the selection criteria participated in this study. The diagnosis of severe mental illness was based on the Mini International Neuropsychiatric Interview (MINI) which was performed by a psychiatrist at the selected clinics. Information on socio-demographic background (age, sex, ethnicity, marital status, level of education, personal and household income), clinical characteristics (types and duration of illness and family history of mental illness and other MetS risk factors), medication consumptions (type and duration of taking medication), lifestyle factors (physical activity level, smoking behavior, alcohol consumption and dietary intake) were collected using a face-to-face interview. Body weight, height, waist circumference, percentage of body fat and blood pressure were measured by the researcher. Fasting glucose, triglycerides and HDL levels of the patients were taken from their respective medical records.Among the 151 outpatients, nearly half of them (48.3%) fulfilled the harmonized criteria for MetS. The prevalence of MetS was high among males (48.5%), married (61.5%), older age group (66.7%) and patients with schizophrenia (50.7%). Age groups (χ2=6.878, p=0.032), marital status (χ2=4.752, p=0.029), duration of illness (χ2=4.215, p=0.040), Vitamn A (χ2=4.159, p=0.041) and body weight status (χ2=29.117, p<0.001) were significantly associated with MetS. Those middle (36–55 years old) and older patients (>55 years old), married, who had been suffering for mental illness for more than 10 years, with inadequate intake of vitamin A, and overweight and obese were more likely to develop MetS than their counterparts. There were no significant associations between sex, ethnicity, educational level, income level, types of illness, physical activity level, smoking behavior, alcohol consumption, social support and social engagement with MetS (p>0.05). Binary logistic regression results showed that only two predictors were significantly associated with MetS, namely the body weight status and age groups. Severe mental illness patients who were overweight (OR=3.8, 95% CI=1.6-9.1) and obese (OR=14.4, 95% CI=4.9-42.6) were approximately 4 times and 14 times more likely to develop MetS, respectively. On the other hand, being a middle and older adult was 3 times (OR=3.0, 95% CI=1.2-7.8) and 5.3 times (OR=5.3, 95% CI=1.4-20.3) more likely to develop MetS, respectively as compared to younger adults. In conclusion, the present study showed a high prevalence of MetS among severe mental illness patients. Age and BMI were found to be the risk factors in the development of MetS. Findings of this study highlight the need of regularly assessing and monitoring MetS and BMI among severe mental illness patients. Intervention programs targeted at preventing and reducing MetS should be planned for severe mental illness patients, especially among those who are overweight and obese and those in middle and older age groups.